2016
DOI: 10.1371/journal.pone.0161175
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin and Melanopsin Contributions to the Early Redilation Phase of the Post-Illumination Pupil Response (PIPR)

Abstract: Melanopsin expressing intrinsically photosensitive Retinal Ganglion Cells (ipRGCs) entirely control the post-illumination pupil response (PIPR) from 6 s post-stimulus to the plateau during redilation after light offset. However, the photoreceptor contributions to the early redilation phase of the PIPR (< 6 s post-stimulus) have not been reported. Here, we evaluated the photoreceptor contributions to the early phase PIPR (0.6 s to 5.0 s) by measuring the spectral sensitivity of the criterion PIPR amplitude in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 52 publications
3
82
1
Order By: Relevance
“…The PIPR amplitude measured > 1.7 s of the light offset reflects melanopsin functions, whereas the early redilation phase of the PIPR < 1.7 s after the light offset has contributions from both, melanopsin and rhodopsin (Adhikari et al, 2016a). The PIPR amplitude increases with increasing retinal irradiance to attain half maximal pupil constriction (> 1.5 mm) at 13.5 log quanta.cm -2 .sec -1 and then plateaus to maximum constriction (> 2.9 mm) at a corneal irradiance of ~ 15 log quanta.cm -2 .sec -1 (Adhikari et al, 2015b;Gamlin et al, 2007;Joyce, Feigl, & Zele, 2012).…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…The PIPR amplitude measured > 1.7 s of the light offset reflects melanopsin functions, whereas the early redilation phase of the PIPR < 1.7 s after the light offset has contributions from both, melanopsin and rhodopsin (Adhikari et al, 2016a). The PIPR amplitude increases with increasing retinal irradiance to attain half maximal pupil constriction (> 1.5 mm) at 13.5 log quanta.cm -2 .sec -1 and then plateaus to maximum constriction (> 2.9 mm) at a corneal irradiance of ~ 15 log quanta.cm -2 .sec -1 (Adhikari et al, 2015b;Gamlin et al, 2007;Joyce, Feigl, & Zele, 2012).…”
Section: Figurementioning
confidence: 95%
“…The PLR is the pupil constriction in response to light and is contributed by both inner retinal ipRGCs and outer retinal rods and cones (Adhikari, Zele, & Feigl, 2015b;Barrionuevo, Nicandro, McAnany, Zele, Gamlin, & Cao, 2014;Joyce, Feigl, Cao, & Zele, 2015;McDougal & Gamlin, 2010) whereas the PIPR, which is a sustained pupil constriction after light offset (Adhikari et al, 2015b;Gamlin et al, 2007;Hansen, Sander, Kessel, Broendsted, Kawasaki, Herbst, LundAndersen, Medicinska, & Oftalmiatrik, 2012;Kankipati, 2009;Kankipati, Girkin, & Gamlin, 2010;Markwell et al, 2010;McDougal et al, 2010;Park, Moura, Raza, Rhee, Kardon, & Hood, 2011;Young & Kimura, 2008), is predominantly driven by ipRGCs (Adhikari, Feigl, & Zele, 2016a;Gamlin et al, 2007). The measurement of the PIPR allows for the direct and in vivo assessment of ipRGC function in humans (Adhikari et al, 2015b;Feigl & Zele, 2014;Gamlin et al, 2007;Kankipati et al, 2010;Markwell et al, 2010;McDougal et al, 2010;Young et al, 2008).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…IpRGCs also signal to the olivary pretectal nucleus (OPN) for mediation of the pupil light reflex (PLR) (Gamlin et al 2007;Kawasaki & Kardon 2007) and in particular the post-illumination pupil response (PIPR) (Adhikari et al 2016a;Gamlin et al 2007;Kawasaki & Kardon 2007;Markwell et al 2010), which is an emerging method for the direct assessment of ipRGC function in healthy and diseased eyes and in persons with chronobiological disorders Feigl et al 2012b;Gamlin et al 2007;Gracitelli et al 2016;Gracitelli et al 2014;Gracitelli et al 2015;Kawasaki & Kardon 2007;Markwell et al 2010;Maynard et al 2015). Two recent studies observed that sleep duration was altered in advanced AMD patients; sleep duration decreased in wet AMD and increased in dry AMD (Khurana et al 2016;Pérez-Canales et al 2016) but the effect of aberrant ipRGC signalling in AMD Maynard et al 2015) as a contributing factor was not evaluated.…”
Section: 3mentioning
confidence: 99%
“…All three photoreceptor types; rods, cones and ipRGCs are affected in advanced AMD (Curcio et al 1996;Maynard et al 2015) and contribute to the initial pupil constriction during stimulus presentation (McDougal & Gamlin 2010) whereas ipRGCs and rods contribute to the sustained post-illumination pupil response (Adhikari et al 2016a;Gamlin et al 2007). At least five different ipRGC subtypes (M 1 -M 5 ) (Ecker et al 2010;Schmidt et al 2011a) have been identified that project to non-image forming centres in the rodent brain, with the M 1 and M 2 subtypes likely to be homologous to the outer and inner stratifying melanopsin cells found in humans and non-human primates (Dacey et al 2005;Jusuf et al 2007;Liao et al 2016).…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation